CAN RELATIONSHIP BENEFITS MAKE CUSTOMERS COMMITTED AND LOYAL? - Fransisca Andreani; Laurencia Jap; Ivana Karina Hosea (Jurnal Manajemen dan Kewirausahaan, 2019)
Tough competition has pushed four-star hotels in Surabaya to manage their competitive strategies. One of them is by providing relational benefits to maintain customer commitment and loyalty. This study is to reveal the impact of relationship benefits on customer loyalty with customer commitment as a mediating variable in four-star hotels in Surabaya. Partial Least Square (PLS) is used to analyze data. It is found that relationship benefits (confidence, social and special treatment benefits) have influenced customer loyalty with commitment as the mediating variable. The results show that relationship benefits have positive and significant impacts to customer commitment; and customer commitment also has positive and significant impact to customer loyalty.